Bone stress and strain after use of a miniplate for molar protraction and uprighting: a 3-dimensional finite element analysis - Largura, Lucila Zimmermann; Argenta, Marco AndrÉ; Sakima, Mauricio Tatsuei [UNESP]; Camargo, Elisa Souza; Guariza-filho, Odilon; Tanaka, Orlando Motohiro (Elsevier, 2014)
The aim of this study was to use the finite element method to evaluate the distribution of stresses and strains on the local bone tissue adjacent to the miniplate used for anchorage of orthodontic forces. Methods: A 3-dimensional model composed of a hemimandible and teeth was constructed using dental computed tomographic images, in which we assembled a miniplate with fixation screws. The uprighting and mesial movements of the mandibular second molar that was anchored with the miniplate were simulated. The miniplate was loaded with horizontal forces of 2, 5, and 15 N. A moment of 11.77 N.mm was also applied. The stress and strain distributions were analyzed, and their correlations with the bone remodeling criteria and miniplate stability were assessed. Results: When orthodontic loads were applied, peak bone strain remained within the range of bone homeostasis (100-1500 mu m strain) with a balance between bone formation and resorption. The maximum deformation was found to be 1035 mu m strain with a force of 5 N. At a force of 15 N, bone resorption was observed in the region of the screws. Conclusions: We observed more stress concentration around the screws than in the cancellous bone. The levels of stress and strain increased when the force was increased but remained within physiologic levels. The anchorage system of miniplate and screws could withstand the orthodontic forces, which did not affect the stability of the miniplate.
Keywords: Orthodontic mini-implants; Skeletal anchorage system; Cortical bone; Histological-evaluation; Miniscrew implants; Surrounding bone; Thickness; Dogs; Placement; Stability; Ancoragem esquelética; Miniplaca; Método do elemento finito; Biomecânica